Jamaica. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Jamaica during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as food safety and health, soil fertility, farmer training, coffee production, biofortified crops, control and biocontrol of pests, such as coffee rust (CLR), the sweet potato weevil and fungi, through beauveria bassiana. Likewise, work was done on conservation management, soil management, through the use of live barriers, reverse slopes and individual basins. Finally, the exchange of knowledge between farmers is supported.